Tundra Bean Geese Anser fabalis rossicus in central and southern Sweden autumn 2009–spring 2012 - Heinicke, Thomas; de Jong, Adriaan (Ornis Norvegica, 2013)
Daytime counts at 35 staging/wintering sites in 2009–2012 revealed that total numbers of Tundra Bean Geese Anser fabalis rossicus present in central and southern Sweden often reached 5000–10000. In mild winters, many of these birds stay in Sweden, mainly in the Hammarsjön area, in NE Scania. These findings show that the current population size of the Taiga Bean Goose A. f. fabalis is seriously over-estimated.